The unnaturalistic fallacy: COVID-19 vaccine mandates should not discriminate against natural immunity - Pugh, J; Savulescu, J; Brown, RCH; Wilkinson, D (BMJ Publishing Group, 2022)
COVID-19 vaccine requirements have generated significant debate. Here, we argue that, on the evidence available, such policies should have recognised proof of natural immunity as a sufficient basis for exemption to vaccination requirements. We begin by distinguishing our argument from two implausible claims about natural immunity: (1) natural immunity is superior to ‘artificial’ vaccine-induced immunity simply because it is ‘natural’ and (2) it is better to acquire immunity through natural infection than via vaccination. We then briefly survey the evidence base for the comparison between naturally acquired immunity and vaccine-induced immunity. While we clearly cannot settle the scientific debates on this point, we suggest that we lack clear and convincing scientific evidence that vaccine-induced immunity has a significantly higher protective effect than natural immunity. Since vaccine requirements represent a substantial infringement of individual liberty, as well as imposing other significant costs, they can only be justified if they are necessary for achieving a proportionate public health benefit. Without compelling evidence for the superiority of vaccine-induced immunity, it cannot be deemed necessary to require vaccination for those with natural immunity. Subjecting them to vaccine mandates is therefore not justified. We conclude by defending the standard of proof that this argument from necessity invokes, and address other pragmatic and practical considerations that may speak against natural immunity exemptions.